Basic concepts of the study of training junior specialists in the service sector on adaptive principles″ - Savielieva, T. (Problems of Engineer-Pedagogical Education, 2019)
In the article the base concepts of research of preparation of junior specialists of sphere of service in professional (vocational) establishments of education are considered. The sphere of service developed and proposes new requirements for preparation of junior specialists of this industry at the labour-market. Necessity arises for forming of new competences of junior specialists of sphere of service, and also updating of maintenance and technologies of their preparation. Such transformations are possible from the side of activation of adaptive processes in creation of educational score in colleges. So in the article paid attention to preparation of junior specialists of sphere of service on principles of adaptivity that will provide ability to change and improve the skills to the graduating student, reacting on the changes of requirements of labour-market. Attention is given to such determination, as a "junior specialist of sphere of service", "maintenance of preparation of junior specialists", "adaptive principles". The defined concepts of research from normatively-legislative, research and practice, literary sources are considered and offer own determinations of terminology taking into account the changes of requirements of labour-market under influence of market economy.